Video Surveillance, Security and the Right to Privacy in Prisons - Batrićević, Ana; Stepanović, Ivana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2020)
The ever-changing technology landscape keeps posing new challenges to privacy protection as smart devices and surveillance mechanisms have the capacity to create large databases of personal information. From public places and private homes to penitentiaries, video surveillance may jeopardize the right to privacy, and it needs to be thoroughly regulated in order to create and maintain a balance between privacy and security. However, video surveillance is not regulated by a specific law in Serbia, which opens a series of disputable issues, especially in the context of prisons, where the decision on the actual manner in which these technologies are applied is made within a particular penitentiary institution. The aim of this paper is to analyse how the right to privacy of prisoners has been conceptualised in international law, to highlight the question of the necessity, advantages and disadvantages of video surveillance in prisons, as well as to raise awareness about the problems that may emerge in this under-regulated field.